2021
DOI: 10.1177/19433875211060931
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Blindness From Facial Trauma: A Multi-Centre Nigerian Study

Abstract: Study Design This is a multi-centre retrospective study. Objective To determine the prevalence of blindness and pattern of facial trauma associated with blindness among Nigerians. Methods A multi-centre retrospective study of all patients with facial trauma resulting in blindness, that were co-managed by maxillofacial surgeons and ophthalmologists in 4 Nigerian public tertiary hospitals between January 2010 and December 2019 was undertaken. Data was analysed by IBM SPSS Statistics (version 21.0 for windows, IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Road traffic accidents are the most common mechanism of facial trauma and cause of blindness in at least one eye. 11 Many factors are associated with an increased risk of traffic accidents, including improved expressways and hence, increased vehicular movement, particularly in low and middle-income countries. It is recommended to implement preventive strategies such as legislation enforcing road traffic safety measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Road traffic accidents are the most common mechanism of facial trauma and cause of blindness in at least one eye. 11 Many factors are associated with an increased risk of traffic accidents, including improved expressways and hence, increased vehicular movement, particularly in low and middle-income countries. It is recommended to implement preventive strategies such as legislation enforcing road traffic safety measures.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previous studies have indicated that an increase in both the age-standardised rates (ASR) of incidence and number of years lived with disability (YLDs) from eye injuries due to intraocular foreign bodies are going to present a global health challenge. 8 , 9 In addition to foreign body injuries, there are many causes of eye injuries, such as explosive eye injuries, 10 road traffic injuries, 11 mechanical or non-mechanical eye injuries (chemical/thermal/radiation), 12 and even self-inflicted injuries. 13 However, the incidence of and burden from eye injury have not been reported, and there has been no information regarding age-, sex-, spatial-, and temporal patterns of eye injury worldwide.…”
Section: Introductionmentioning
confidence: 99%